STRATEGI PENGEMBANGAN EKOWISATA BERBASIS MASYARAKAT DI KAWASAN DESA AIQ BERIQ KECAMATAN BATUKLIANG UTARA KABUPATEN LOMBOK TENGAH - Rachman, Irna Ningsi Amalia; Badi'ah, Baiq Arriyadul; Usman, Kemas (Jurnal Silva Samalas, 2026)
This study aims to analyze the development strategy of community-based ecotourism (CBET) in Aiq Beriq Village, Batukliang Utara District, Central Lombok Regency. The village possesses rich natural and cultural tourism potential, notably the Benang Stokel and Benang Kelambu waterfalls, which serve as valuable assets for sustainable tourism development. This research employed a qualitative exploratory case study approach, using data collection methods including participatory observation, in-depth interviews, and documentation. Data were analyzed through reduction, thematic categorization, source triangulation, and SWOT analysis. The findings indicate that community participation through Pokdarwis (Tourism Awareness Groups), village authorities, and local managers plays a crucial role in improving local livelihoods while promoting environmental conservation. The SWOT analysis reveals that the main strengths of the area lie in its natural beauty, local wisdom, and institutional support from the village government, whereas weaknesses include limited human resources and inadequate infrastructure. Development strategies are directed toward strengthening community capacity, enhancing digital tourism promotion, and establishing environmental conservation regulations. This study concludes that the ecotourism development in Aiq Beriq represents a concrete practice of sustainable development, integrating economic, social, cultural, and ecological dimensions in a synergistic manner.